2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9175272
|View full text |Cite
|
Sign up to set email alerts
|

Band Electrodes Reduce Simulated Calf Bioimpedance Measurement Errors Due to Muscle Anisotropy

Abstract: Remote monitoring of fluid status via calf bioimpedance measurements could improve the experience of patients with congestive heart failure and reduce readmission rates. Most measurements today use conventional Ag/AgCl electrodes and a short inter-electrode spacing, resulting in current flowing primarily near the electrodes, preventing deeper current penetration and in turn accurate volume estimation. Textile band electrodes may more evenly distribute current throughout the calf. In the present study, simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…One is to reduce the difference between χ 3 or χ 4 in some way, but this can be difficult in practice due to limitations of electrode materials. However, there are alternative methods: (1) adjusting the cutoff frequency (increasing the LF or reducing the HF) before fitting to the Cole model and (2) performing the measurement twice, swapping the voltage and current leads 1 For a detailed derivation and discussion on how the resistances and other parameters contribute to overall errors in fluid status estimation, see [8].…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…One is to reduce the difference between χ 3 or χ 4 in some way, but this can be difficult in practice due to limitations of electrode materials. However, there are alternative methods: (1) adjusting the cutoff frequency (increasing the LF or reducing the HF) before fitting to the Cole model and (2) performing the measurement twice, swapping the voltage and current leads 1 For a detailed derivation and discussion on how the resistances and other parameters contribute to overall errors in fluid status estimation, see [8].…”
Section: A Backgroundmentioning
confidence: 99%
“…One of the major challenges in bioimpedance research is the lack of electrodes that can be used for long-term monitoring, especially in home environments. Previous research has shown that textile band electrodes are a promising alternative to conventional Ag/AgCl electrodes and can be used for segmental bioimpedance measurements at the calf [1]. However, textile electrodes have artifacts that can prevent accurate volume estimation [2].…”
Section: Introductionmentioning
confidence: 99%
“…The wearable compression sock consisted of four band electrodes made from a textile material to ensure uniform current distribution throughout the measured part of the calf. A uniform current distribution is necessary in order to estimate volume based on bioimpedance (see Section 2.1), and to ensure that bioimpedance is not artificially high due to fat on the calf (Delano, 2020). Band electrodes ensure this uniformity by driving current through the calf from around the calf circumference, rather than from a single point as with spot Ag/AgCl electrodes.…”
Section: Textile Designmentioning
confidence: 99%
“…1. Current distribution: The prototype uses band electrodes to distribute current uniformly through the calf, minimizing the impact of calf fat and ensuring accurate calf fluid volume estimation, unlike conventional spot Ag/AgCl electrodes (Delano, 2020).…”
Section: Introductionmentioning
confidence: 99%